Extension of coverage period from 5th March, 2020 to 31st December, 2022 - Bangladesh General Insurance Company Ltd. (BGIC) (Brac University, 2023)
This record consists of general correspondence regarding Workmen's compensation insurance policy between Brac University and BUCG for BRACU new campus project.